2019
DOI: 10.1089/ten.tea.2018.0130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Beam Sterilization on Three-Dimensional-Printed Polycaprolactone/Beta-Tricalcium Phosphate Scaffolds for Bone Tissue Engineering

Abstract: Three-dimensional printing of composite materials such as polycaprolactone/beta-tricalcium phosphate (PCL/b-TCP) enables the design and manufacturing of scaffolds with advanced geometries, along with improved physical and biological properties for large bone defect repair. Terminal sterilization of the scaffolds is inevitable for clinical applications. Electron beam (E-beam) is nontoxic, and can be used for sterilizing heatsensitive scaffolds by the use of high radiation dose in a short period of time. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…In our previous study, we found a 14% increase in the initial Young's modulus and a 25% faster in vitro degradation profile for scaffolds that received E-beam compared to those that did not [23]. The increased Young's modulus values after E-beam were likely due to crosslinking, which strengthens the β-TCP/PCL composite structure, while the increase in degradation rate after E-beam in vitro was likely due to chain scissioning, which is thought to weaken the composite structure [23].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In our previous study, we found a 14% increase in the initial Young's modulus and a 25% faster in vitro degradation profile for scaffolds that received E-beam compared to those that did not [23]. The increased Young's modulus values after E-beam were likely due to crosslinking, which strengthens the β-TCP/PCL composite structure, while the increase in degradation rate after E-beam in vitro was likely due to chain scissioning, which is thought to weaken the composite structure [23].…”
Section: Introductionmentioning
confidence: 84%
“…In our previous study, we found a 14% increase in the initial Young's modulus and a 25% faster in vitro degradation profile for scaffolds that received E-beam compared to those that did not [23]. The increased Young's modulus values after E-beam were likely due to crosslinking, which strengthens the β-TCP/PCL composite structure, while the increase in degradation rate after E-beam in vitro was likely due to chain scissioning, which is thought to weaken the composite structure [23]. Furthermore, since β-TCP particles are merely suspended in the polymer matrix, degradation of β-TCP/PCL scaffolds in any given solution is mainly driven by polymer degradation via the hydrolytic cleavage or scissioning of ester-ester linkages [19,20,23,25].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations